A SERVICE AND COMPLAINT SYSTEM IMPROVEMENT WITH NEW METHOD - Dedi Purwanto; Yossi Fadly; Rian Farta Wijaya; Abdu Rangga Senjari (Jurnal Scientia, 2023)
The University Quality Assurance Center is a work unit at Pembangunan Panca Budi University which has duties and functions in the field of Quality Assurance which provides direct services to students, lecturers and the public for complaints of academic and non-academic violations. Students, lecturers and the community need a service or facility to make it easier to submit questions and complaints related to academic and non-academic violations which of course hope to get answers directly from those who are experts in their fields. So far, the PPMU academic and non-academic violation complaint service management system uses the Google Form System where the features on the Google form cannot meet the desired needs, such as (1) Communication cannot be done in two directions or is only providing input/filling in the Google form, (2) Incoming complaint data requires managers to recap or tabulate data as needed, (3) Limited design such as only 4 types of font variations, (4) No email notifications when respondents complete complaint reports on the Google form, (5) None history of editing modifications means that you cannot see the changes that have been made to the form, even though a good application is built according to the needs required by the agency, based on this the author feels the need to build a flexible mobile-based application, namely data communication between backend and frontend applications using API (Application Programming Interface) methods in HTTP Header and JSON (JavaScript Object Notation) formats.